Funciones del Banco Central del Ecuador en dolarización a oficial de la economía - Hidalgo, Francisco (2002)
The application of a process of official dollarization of an economy means much more than a variation in the monetary regime or in the exchange rate regime, it actually means the implementation of a new economic system that goes beyond the monetary and exchange scope and that It has strong implications for public finances, foreign trade, competitiveness, real investment, growth, interest rates, inflation, sovereign risk, the financial sector, etc. The official dollarization of an economy. therefore, it should not be considered as an alternative exchange regime, similar to the previous ones applied; such as, for example, mini devaluations, discretionary devaluations, controlled floating, exchange rate bands, among others, because, objectively, in official dollarization there is no exchange rate in the strict sense.